FOOD AND LIVING HABITS OF DIABETIC PATIENTS TYPE 2 MONITORED TO DEPARTMENTAL HOSPITAL CENTER (CHD) ATACORA (BENIN). - konfo, Christian Tétédé Rodrigue (Journal of Biomedical and Pharmaceutical Research, 2019)
Rapid urbanization and the globalization of the food market have led to changes in nutritional behavior and the way of life of populations, including developing countries such as Benin, with the consequent emergence of various pathologies such as diabetes type 2. The aim of this study was to study the food profile and lifestyle of type 2 diabetic patients followed by CHD-Atacora from Natitingou, Benin.It was a cross-sectional study with a descriptive and analytical purpose. Sociodemographic, biometric and dietary information were collected on the basis of a pre-established and validated questionnaire. A total of 204 type 2 diabetic patients were enrolled in the study. The mean age of the subjects was 56 ± 12 years with female predominance (sex-ratio = 1.5). The Wama, Bariba and Ditamari ethnic groups accounted for 43% of the sample. Almost 75% have a level of education less than or equal to secondary school. The main comorbidities were abdominal obesity (90%) and high blood pressure (48%). About 70% of the subjects reported that they regularly engage in physical activity, including walking (60%). Cereal-based foods (maize, rice, millet and sorghum) and vegetable sauces largely dominate the food consumed by the subjects (90%). Food habits including cereal-based foods, mainly maize seem to have a definite impact on the management of the disease. Educational attainment would also be a key factor to consider as higher educated individuals appear to be more aware of the influence of food habits and lifestyle on diabetes management.